The RF in RFID passive UHF RFID in practice - Dobkin, Daniel Mark (Elsevier / Newnes, 2008)
This book includes a survey of all RFID fundamentals and practices in the first part of the book while the second part focuses on UHF passive technology. This coverage of UHF technology and its components including tags, readers, and antennas is essential to commercial implementation in supply chain logistics and security. Reaaders of this book should have an electrical engineering background but have not yet dealt with RFID. To this end, Dr. Dobkin will be very careful to illustrate all concepts and detail his explanations meticulously. In this way he will bring the reader along organically showing him/her what to expect, develop, and use while implementing an RFID system. Chapter 1:Introduction Chapter 2: History and Practice of RFID Chapter 3: Radio Basics For UHF RFID Chapter 4: UHF RFID Readers Chapter 5: UHF RFID Tags Chapter 6: Reader Antennas Chapter 7: Tag Antennas Chapter 8: UHF RFID Protocols Afterword Appendix 1: Radio Regulations Appendix 2: Harmonic Functions Appendix 3: Resistance, Impedance and Switching Appendix 4: Reflection and Matching *This technology is happening NOW at major chain stores such as Wal-Mart and Target *RFID revenues are estimated to soar about $7 billion by 2008 *CD-ROM included with full color images, spreadsheets, an open-source example graphical user interface, and demo versions of commercial software.
Keywords: Radio frequency identification systems.; Radio frequency -- Identification.; Wireless communication systems.; elektronické knihy; electronic books